THE SIGNIFICANCE OF UNDERSTANDING PARTS OF SPEECH FOR EFFECTIVE COMMUNICATION - Jumanazarov Bakhram Mengqobil o‘g‘li (Web of Journals Publishing, 2025)
The article highlights the importance of parts of speech in English, both in writing and speaking. It discusses how mastering these components can enhance language skills, improve grammar, and aid in the development of more complex sentence structures. Additionally, the piece addresses common challenges learners face when identifying and using different parts of speech, offering practical examples and tips for overcoming these obstacles.
Keywords: Effective communication; enhance language skills; sentence structures; linguistic features; different parts of speech; language community.